Meanings attributed to PIBID: dialogue with a teacher from the UFSCar-Sorocaba - Francisco Nunes de Brito, Valtair (Seven Editora, 2023)
The work aims to understand the meanings attributed by a Geography professor who participated in the Pibid-UFSCar between 2010-2011. The research uses a qualitative approach and data collection through semi-structured interviews. In the interview, the graduate showed activities that he participated and the legacy obtained for his career. The respondent commented on their respective participations as a student and observer of the planning and practices developed at the school as a Pibid scholarship. We also tried to understand if the collaborative training between university and school allowed the graduate to perceive the challenges and interferences present in daily school life and that limit professional autonomy. Through Content Analysis, categories emerged such as: interdisciplinarity, curriculum and dispute, planning and school diagnosis. We also noticed cases in which Pibid acted as an inducer of research in education. DOI: 10.56238/pacfdnsv1-114